2022
DOI: 10.3390/cells11182913
|View full text |Cite
|
Sign up to set email alerts
|

Small Extracellular Vesicles and Their Involvement in Cancer Resistance: An Up-to-Date Review

Abstract: In recent years, tremendous progress has been made in understanding the roles of extracellular vesicles (EVs) in cancer. Thanks to advancements in molecular biology, it has been found that the fraction of EVs called exosomes or small EVs (sEVs) modulates the sensitivity of cancer cells to chemotherapeutic agents by delivering molecularly active non-coding RNAs (ncRNAs). An in-depth analysis shows that two main molecular mechanisms are involved in exosomal modified chemoresistance: (1) translational repression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 175 publications
0
15
0
Order By: Relevance
“…EVs are nanosized particles constantly secreted by all cells and their features reflect the state of the cell of origin, so that they can mirror tissue health and disease [ 22 , 23 , 24 ]. From a clinical perspective, EVs can be used as appropriate biomarkers to evaluate disease evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs are nanosized particles constantly secreted by all cells and their features reflect the state of the cell of origin, so that they can mirror tissue health and disease [ 22 , 23 , 24 ]. From a clinical perspective, EVs can be used as appropriate biomarkers to evaluate disease evolution.…”
Section: Discussionmentioning
confidence: 99%
“…It could be speculated that uEV cargo during DN may be involved in the amplification of diabetic-induced alterations via EV release or, alternatively, simply represent the modulation of the miRNA packaging in EVs from damaged renal cells. Understanding these intracellular mechanisms and precisely following the axis of miRNA-messenger RNA in kidney cells [ 23 , 24 , 25 , 36 ] is crucial for the future use of EVs in the clinical evaluation of DN. Further experiments are needed to clarify this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exosomal lncRNA-HNF1A-AS1 has not been widely studied in the literature. Luo et al reported that exosomal lncRNA-HNF1A-AS1 secreted by the cisplatin-resistant cells could inhibit apoptosis of cervical tumors [ 42 , 43 ]. Moreover, the inhibition of exosomal lncRNA-HNF1A-AS1 could inhibit tumor formation in nude mice [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unless here we focused on an axis involving (non-coding and coding) RNA molecules, data obtained on the expression of VEGFA mRNA suggest that IGFBP2 may be upstream regulated by circSMARCA5 also at the protein level: indeed, IGFBP2 was described as an enhancer for the transcription of VEGFA in neuroblastoma cells [ 93 ] and IGFBP2 and VEGFA were shown to be positively correlated at the protein level in GBM tissues [ 94 ]. MiR-126-3p can be also carried in biological fluids through EVs [ 95 , 96 ]: it would be interesting to investigate if and how the delivery of this molecule to cells at different sites from the bulk tumor play a role in the cancer progression and resistance to the current therapies. MiR-515-5p and its target NRAS are also known to be involved in GBM progression by regulating cell migration, growth [ 53 , 54 , 55 , 56 , 97 ], and angiogenesis [ 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%